2004
DOI: 10.1529/biophysj.104.040550
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Kv1.2 Intracellular Regions on Activation of Kv2.1 Channels

Abstract: Depolarizing voltage steps activate voltage-dependent K(+) (Kv) channels by moving the voltage sensor, which triggers a coupling reaction leading to the opening of the pore. We constructed chimeric channels in which intracellular regions of slowly activating Kv2.1 channels were replaced by respective regions of rapidly activating Kv1.2 channels. Substitution of either the N-terminus, S4-S5 linker, or C-terminus generated chimeric Kv2.1/1.2 channels with a paradoxically slow and approximately exponential activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 42 publications
4
16
0
Order By: Relevance
“…The interaction between N and C termini of several Kv channels, including Shaker, Kv1.2 and Kv2.1, has been suggested before (Schulteis et al, 1996;Ju et al, 2003;Scholle et al, 2004;Long et al, 2005;Kobrinsky et al, 2006). In this study, we have provided evidence that the N/C terminal interaction of Kv3.1 channels is mediated by a direct, Zn 2ϩ -dependent binding between the T1 domain and the ATM region (Figs.…”
Section: Direct Interaction Between the T1 Domain And The Atm Regionsupporting
confidence: 64%
“…The interaction between N and C termini of several Kv channels, including Shaker, Kv1.2 and Kv2.1, has been suggested before (Schulteis et al, 1996;Ju et al, 2003;Scholle et al, 2004;Long et al, 2005;Kobrinsky et al, 2006). In this study, we have provided evidence that the N/C terminal interaction of Kv3.1 channels is mediated by a direct, Zn 2ϩ -dependent binding between the T1 domain and the ATM region (Figs.…”
Section: Direct Interaction Between the T1 Domain And The Atm Regionsupporting
confidence: 64%
“…The activation gating of a number of ion channels, especially whose gating is influenced by intracellular ligand binding [e.g., cyclic nucleotide gated channels (Gordon et al, 1997;Varnum and Zagotta, 1997;Zheng et al, 2003) and cystic fibrosis transmembrane conductance regulator channels (Naren et al, 1999)], involves N/C interaction. Previous mutational analyses of the effects of N-and C-terminal deletions (VanDongen et al, 1990), point mutations (Ju et al, 2003), and chimeras (Scholle et al, 2004;Mohapatra and Trimmer, 2006) suggested a role for N/C interaction in regulating Kv2.1 voltage-dependent activation, and a direct interaction between Kv2.1 N and C termini has been suggested from in vitro binding studies (Bentley et al, 1999). Voltage-dependent Kv2.1 activation is also profoundly affected by extensive in vivo Kv2.1 C-terminal phosphorylation .…”
Section: Discussionmentioning
confidence: 99%
“…Although they were constructed as nucleotide sequence corresponding to amino acid residues from 411 to 853, the actual start point is at residue M444, the first corresponding 5Ј-ATG sequence in these constructs. Kv2.1-⌬C416-Kv1.2-S4-S5 chimera was generated from the chimera of Kv2.1 with S4 -S5 sequence of Kv1.2 (Scholle et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The crystal structure of the T1 domain is known and forms a tetramer below the membrane like a "hanging gondola" (7), while the C-terminal domain surrounds this N-terminal structure (8). There are voltage-dependent interactions between the N terminus and the C terminus that are important determinants of channel activation and modulate the activation time course of K v ␣ channels (6,9).…”
mentioning
confidence: 99%